A philosophical analysis of tembang macapat: Javanese and islamic perspective - Ngatmin Abbas; Mukhlis Fathurrohman; Amir Mahmud; Habib Assalam (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This research explores the philosophical meaning of Macapat songs in the context of Javanese and Islamic culture using a hermeneutic approach. Macapat songs, such as Maskumambang, Mijil, Sinom, and Kinanthi, are part of Javanese oral literary heritage that contains ethical, spiritual, and social values that remain relevant in modern life. The research method used is library research, analyzing various literature discussing Macapat songs from cultural and Islamic perspectives. The results show that Macapat songs can function as a means to build Islamic moderation, through integrating Javanese cultural values and Islamic teachings. The hermeneutic approach provides a deeper understanding of the symbolism found in Macapat songs, so that it can be used as a reference in shaping an inclusive and balanced community character. The implications of this research contribute to the development of cultural and Islamic studies, as well as utilizing Macapat songs in moral and spiritual education for Javanese society.